Law Application To Children As Narcotics Abuse Persons - Danang Halintoko; Marfendi Oktavianto Pratama; Ombun Simatupang; Hanang Wahyu Anshori; Sufiarina Sufiarina (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2023)
Typical psychological characteristics of adolescents are factors that facilitate substance abuse. However, for this to happen there are other factors that play an important role, namely the environmental factors of the substance user. These environmental factors have an influence on adolescents and trigger the emergence of motivation to abuse substances. In other words, the emergence of substance abuse problems is triggered by the interaction between environmental influences and the psychological condition of adolescents. The approach used in this study is a normative juridical approach. Normative Juridical Research Method is legal research that uses secondary data sources. As a legal (juridical) research with the object of juvenile law principles, the approach used is a juridical approach, namely formal juridical and empirical juridical approaches. Legal protection for children in the judicial process is carried out starting from the level of investigation, investigation, prosecution, examination at court hearings up to the implementation of the court decision. During the judicial process, the rights of the child must be protected by applicable law and therefore it must be carried out consistently by the parties involved in solving the problem of the naughty child.